Genome-Wide Study of the Tomato SlMLO Gene Family and Its Functional Characterization in Response to the Powdery Mildew Fungus Oidium neolycopersici - Zheng, Zheng; Appiano, Michela; Pavan, Stefano; Bracuto, Valentina; Ricciardi, Luigi; Visser, Richard G. F.; Wolters, Anne-Marie A.; Bai, Yuling (Frontiers in Plant Science, 2016)
The MLO (Mildew Locus O) gene family encodes plant-specific proteins containing seven transmembrane domains and likely acting in signal transduction in a calcium and calmodulin dependent manner. Some members of the MLO family are susceptibility factors towards fungi causing the powdery mildew disease. In tomato, for example, the loss-of-function of the MLO gene SlMLO1 leads to a particular form of powdery mildew resistance, called ol-2, which arrests almost completely fungal penetration. This type of penetration resistance is characterized by the apposition of papillae at the sites of plant-pathogen interaction. Other MLO homologs in Arabidopsis regulate root response to mechanical stimuli (AtMLO4 and AtMLO11) and pollen tube reception by the female gametophyte (AtMLO7). However, the role of most MLO genes remains unknown. In this work, we provide a genome-wide study of the tomato SlMLO gene family. Besides SlMLO1, other fifteen SlMLO homologs were identified and characterized with respect to their structure, genomic organization, phylogenetic relationship, and expression profile. In addition, by analysis of transgenic plants, we demonstrated that simultaneous silencing of SlMLO1 and two of its closely related homologs, SlMLO5 and SlMLO8, confer higher level of resistance than the one associated with the ol-2 mutation. The outcome of this study provides evidence for functional redundancy among tomato homolog genes involved in powdery mildew susceptibility. Moreover, we developed a series of transgenic lines silenced for individual SlMLO homologs, which lay the foundation for further investigations aimed at assigning new biological functions to the MLO gene family.